The Expositor's Bible: The Books of Chronicles - Bennett, W. H. (William Henry), 1855-1920 (Salt Lake City, UT : Project Gutenberg, 2012)
"The Expositor's Bible: The Books of Chronicles" by W. H. Bennett is a scholarly exposition written in the early 20th century. The work examines the biblical texts of the Books of Chronicles, focusing on their historical context, authorship, and the spiritual significance of their content. The author, a professor of Old Testament Languages and Literature, aims to analyze the stories, genealogies, and rituals within Chronicles. The opening of the book introduces the author$1 (Bs methodological approach, emphasizing the need to understand Chronicles in relation to its contemporaneous texts, specifically Ezra and Nehemiah. Bennett highlights the intricate connections between Chronicles and older historical sources while noting the chronicler's interest in genealogy and the ecclesiastical structure of the Jewish community. He discusses the distinctions between the existing genealogies, their implications for social identity in the post-exilic Jewish community, and the chronicler's unique perspective on history as a vehicle for spiritual teaching, setting the stage for a deeper exploration of the themes and narratives within the Chronicles. (This is an automatically generated summary.)s
Release date is 2012-07-14
Keywords: Bible. Chronicles -- Commentaries